Numerical studies of diffusion and amplification of magnetic fields in turbulent astrophysical plasmas - Lima, Reinaldo Santos de (2013)
In this thesis we investigated two major issues in astrophysical flows: the transport of magnetic fields in highly conducting fluids in the presence of turbulence, and the turbulence evolution and turbulent dynamo amplification of magnetic fields in collisionless plasmas. The first topic was explored in the context of star-formation, where two intriguing problems are highly debated: the requirement of magnetic flux diffusion during the gravitational collapse of molecular clouds in order to explain the observed magnetic field intensities in protostars (the so called \"magnetic flux problem\") and the formation of rotationally sustained protostellar discs in the presence of the magnetic fields which tend to remove all the angular momentum (the so called \"magnetic braking catastrophe\"). Both problems challenge the ideal MHD description, usually expected to be a good approximation in these environments. The ambipolar diffusion, which is the mechanism commonly invoked to solve these problems, has been lately questioned both by observations and numerical simulation results. We have here investigated a new paradigm, an alternative diffusive mechanism based on fast magnetic reconnection induced by turbulence, termed turbulent reconnection diffusion (TRD). We tested the TRD through fully 3D MHD numerical simulations, injecting turbulence into molecular clouds with initial cylindrical geometry, uniform longitudinal magnetic field and periodic boundary conditions. We have demonstrated the efficiency of the TRD in decorrelating the magnetic flux from the gas, allowing the infall of gas into the gravitational well while the field lines migrate to the outer regions of the cloud. This mechanism works for clouds starting either in magnetohydrostatic equilibrium or initially out-of-equilibrium in free-fall. We estimated the rates at which the TRD operate and found that they are faster when the central gravitational potential is higher. Also we found that the larger the initial value of the thermal to magnetic pressure ratio (beta) the larger the diffusion process. Besides, we have found that these rates are consistent with the predictions of the theory, particularly when turbulence is trans- or super-Alfvénic. We have also explored by means of 3D MHD simulations the role of the TRD in protostellar disks formation. Under ideal MHD conditions, the removal of angular momentum from the disk progenitor by the typically embedded magnetic field may prevent the formation of a rotationally supported disk during the main protostellar accretion phase of low mass stars. Previous studies showed that an enhanced microscopic diffusivity of about three orders of magnitude larger than the Ohmic diffusivity would be necessary to enable the formation of a rotationally supported disk. However, the nature of this enhanced diffusivity was not explained. Our numerical simulations of disk formation in the presence of turbulence demonstrated the efficiency of the TRD in providing the diffusion of the magnetic flux to the envelope of the protostar during the gravitational collapse, thus enabling the formation of rotationally supported disks of radius ~ 100 AU, in agreement with the observations. The second topic of this thesis has been investigated in the framework of the plasmas of the intracluster medium (ICM). The amplification and maintenance of the observed magnetic fields in the ICM are usually attributed to the turbulent dynamo action which is known to amplify the magnetic energy until close equipartition with the kinetic energy. This is generally derived employing a collisional MHD model. However, this is poorly justified a priori since in the ICM the ion mean free path between collisions is of the order of the dynamical scales, thus requiring a collisionless-MHD description. We have studied here the turbulence statistics and the turbulent dynamo amplification of seed magnetic fields in the ICM using a single-fluid collisionless-MHD model. This introduces an anisotropic thermal pressure with respect to the direction of the local magnetic field and this anisotropy modifies the MHD linear waves and creates kinetic instabilities. Our collisionless-MHD model includes a relaxation term of the pressure anisotropy due to the feedback of the mirror and firehose instabilities. We performed 3D numerical simulations of forced transonic turbulence in a periodic box mimicking the turbulent ICM, assuming different initial values of the magnetic field intensity and different relaxation rates of the pressure anisotropy. We showed that in the high beta plasma regime of the ICM where these kinetic instabilities are stronger, a fast anisotropy relaxation rate gives results which are similar to the collisional-MHD model in the description of the statistical properties of the turbulence. Also, the amplification of the magnetic energy due to the turbulent dynamo action when considering an initial seed magnetic field is similar to the collisional-MHD model, particularly when considering an instantaneous anisotropy relaxation. The models without any pressure anisotropy relaxation deviate significantly from the collisional-MHD results, showing more power in small-scale fluctuations of the density and velocity field, in agreement with a significant presence of the kinetic instabilities; however, the fluctuations in the magnetic field are mostly suppressed. In this case, the turbulent dynamo fails in amplifying seed magnetic fields and the magnetic energy saturates at values several orders of magnitude below the kinetic energy. It was suggested by previous studies of the collisionless plasma of the solar wind that the pressure anisotropy relaxation rate is of the order of a few percent of the ion gyrofrequency. The present study has shown that if this is also the case for the ICM, then the models which best represent the ICM are those with instantaneous anisotropy relaxation rate, i.e., the models which revealed a behavior very similar to the collisional-MHD description.